HUBUNGAN TERPAAN PROGRAM USAHA PENINGKATAN PENDAPATAN KELOMPOK AKSEPTOR (UPPKA) DAN TINGKAT PENDIDIKAN DENGAN PERILAKU USAHA KELUARGA AKSEPTOR DI KAMPUNG KOKOLAKA, KECAMATAN GUNUNGPATI, KOTA SEMARANG - Imam Fahmidin, Hanif; Lukmantoro, Yanuar; Setyabudi, Djoko (Interaksi Online, 2024)
Based on the low participation rates of the Income-Generating Program for Acceptor Groups (UPPKA) in the Kampung KB of Kokolaka, Semarang City. Due to a numerous potential of local-based economic growth empowerment, ideally, there should be 200 SMEs, resulting from the BKKBN promotional efforts for economic improvement of the acceptor’s family in the Kokolaka village through the program. According to the data, 54 percent of the household head in the Kokolaka village had finished primary to secondary education, and only a small proportion had finished tertiary education/university degree. The aim of this study is to understand the association between the program exposure, educational attainment, and the behavior to improve their income. This study employed a quantitative, explanatory method. Data collection was done using interview methods to 100 respondents with inclusion criterias of: 1) ever been exposed to the information of the UPPKA program from the BKKBN; 2) understand the program algorithm and the management of the UPPKA program, and 3) resided in the Kokolaka village. The result from this study found that there were positive associations between information exposure and the behavior to improve economy, using Kendall’s Tau-b test. This result was also support by the significance score of 0.251, showing a low strength of correlation. This finding aligned with the applied Theory of Reasoned Action. However, the educational attainment of the Kokolaka village was not associated with the behavior to improve their income as the output of the program.